A Suzaku X-ray study of the mixed-morphology supernova remnant Kes 69 and searching for its gamma-ray counterpart. Issue 1 (31st August 2018) - Sezer, A; Ergin, T; Yamazaki, R; Ohira, Y; Cesur, N
ABSTRACT: Kes 69 is a mixed-morphology (MM) supernova remnant (SNR) that is known to be interacting with molecular clouds based on 1720 MHz hydroxyl (OH) maser emission observations in the northeastern and southeastern regions. We present an investigation of Kes 69 using ∼67 ks Suzaku observation. The X-ray spectrum of the whole SNR is well fitted by a non-equilibrium ionization model with an electron temperature of kT e ∼ 2.5 keV, ionization time-scale of τ ∼ 4.1 × 10 10 cm −3 s and absorbing column density of N H ∼ 3.1 × 10 22 cm −2 . We clearly detected the Fe–K α line at ∼6.5 keV in the spectra. The plasma shows slightly enhanced abundances of Mg, Si, S, and Fe indicating that the plasma is likely to be of ejecta origin. We find no significant feature of a recombining plasma in this SNR. In order to characterize radial variations in the X-ray spectral parameters, we also analyse annular regions in the remnant. We investigate the explosive origin of Kes 69 and favour the core-collapse origin. Additionally, we report a lack of significant gamma-ray emission from Kes 69, after analysing the GeV gamma-ray data taken for about 9 yr by the Large Area Telescope on board Fermi . Finally, we discuss the properties of Kes 69 in the context of other interacting MM SNRs.